Perancangan Usulan Model Bisnis pada PT ABC Gudang Pondok Aren Menggunakan Metode Business Model Canvas - Ayu Maharani Sekar Swastini, Ni Luh; Aryani, Sinta; Sulistyo, Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
PT ABC is a company that distributes fresh cut chicken with premium quality broiler chickens which supplies chicken meat for hotels, restaurants, cafes, factories, processed chicken meat, government and private agencies, as well as household needs. There are 5 warehouse locations, namely Jatiasih, Pondok Aren, Batuceper, North Bekasi, and Pasar Minggu. However, this research focuses on discussing the problems that exist at PT ABC Gudang Pondok Aren. In running its business, PT ABC Gudang Pondok Aren has a main problem, namely a decline in sales caused by a decrease in total customers. Through this main problem, a fishbone is obtained which contains the roots of the problem from the man, method, facility, information and product factors. Based on the main problem and the roots of the problem, to overcome the existing problems at PT ABC it is necessary to evaluate and design a proposed new business model that can contribute to future business development. Based on these problems, the solution used in this research uses the Business Model Canvas (BMC) method. There is a supporting theoretical basis such as business model theory, Business Model Canvas (BMC), business environment strategy, SWOT analysis, SWOT matrix and value proposition canvas. The results obtained are in the form of a proposed Business Model Canvas (BMC) which provides solutions in the form of additional services, additional products new products, changes in packaging methods, and suggestions in terms of product marketing.